2020
DOI: 10.1017/bpp.2020.42
|View full text |Cite
|
Sign up to set email alerts
|

How social norms are often a barrier to addressing climate change but can be part of the solution

Abstract: We argue that the behavioral challenges posed by climate change are fundamentally problems of social influence. Behaviors that perpetuate climate change are often opaque in their consequences; thus, we look to others to infer how to act. Yet unsustainable behaviors, like driving and eating meat, are often the norm; conformity to such norms is a major hurdle to a more sustainable world. Nonetheless, we argue that social norms can also be a powerful lever for positive change. Drawing on two streams of recent res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
53
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 88 publications
(71 citation statements)
references
References 123 publications
0
53
0
1
Order By: Relevance
“…The perspective developed here may encourage individuals to look out for signs of accelerating social dynamics (e.g., in media discourse), which could become windows of opportunity for systemic change. Motivation to participate in changing social norms may be higher when individuals see themselves as effectively "pushing" a change process, which is already ongoing (Sparkman et al, 2020). At the moment, individuals in Western societies will often not be aware of these notions, a fact which can be seen as an effect of the dominance of individualistic paradigms described by Göpel (2016).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The perspective developed here may encourage individuals to look out for signs of accelerating social dynamics (e.g., in media discourse), which could become windows of opportunity for systemic change. Motivation to participate in changing social norms may be higher when individuals see themselves as effectively "pushing" a change process, which is already ongoing (Sparkman et al, 2020). At the moment, individuals in Western societies will often not be aware of these notions, a fact which can be seen as an effect of the dominance of individualistic paradigms described by Göpel (2016).…”
Section: Discussionmentioning
confidence: 99%
“…As stated above, social norms as a form of social influence are embedded in our social communities (Sparkman et al, 2020). Theories like the Social Identity Theory (Tajfel and Turner, 1986) help to explain normative influence and norm salience in a particular situation highlighting the importance of "behaviorally relevant ingroups" (Fielding and Louis, 2020).…”
Section: Psychological Approaches To Conceptualizing the Role Of Individual Agency In Mobility Transitionmentioning
confidence: 99%
See 1 more Smart Citation
“…Third, future research should also assess the risks of potentially negative feedback effects. For instance, previous research has shown that norm messages communicating the prevalence of non-sustainable behaviors can decrease policy support and increase unsustainable behaviors 51,52 . Finally, consumers' misperceptions of their food waste contributions might explain why citizens support supply-side policies that set stringent reduction targets for the food industry but oppose demand-side policies that directly target consumers 11 .…”
Section: Implications For Policymaking and Future Research On Food Wastementioning
confidence: 99%
“…One key insight from this special issue is the importance of the social context in which people make consumer decisions. For example, Sparkman et al (this issue) point out that, as a social dilemma, climate change is fundamentally a problem of vicious and virtuous behaviour cycles. Critically, Sparkman and colleagues highlight that many unsustainable behaviours, such as driving and meat consumption, remain the current norm.…”
Section: Policy Interventions For Consumer Behaviourmentioning
confidence: 99%